1988
DOI: 10.1159/000099977
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Cerebrospinal Fluid Opioids and Neurotransmitters Related to Spinal Cord Stimulation

Abstract: The purpose of this study was to assess the biochemical mechanisms underlying spinal cord stimulation (SCS). Seventeen patients with chronic pain were investigated by measuring cerebrospinal fluid concentrations of endogenous opioids and biogenic amines before and during dorsal column stimulation. BasaI cerebrospinal fluid β-endorphin levels were below the normal range. No significant change of norepinephrine, epinephrine, dopamine, β-endorphin, β-lipotropin, or adrenocorticotropic hormone levels were found af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
5

Year Published

1992
1992
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 0 publications
1
27
0
5
Order By: Relevance
“…The levels of dopamine and adrenaline were unaffected in this study (but were elevated in plasma). There are also some studies with conflicting results published [8,19,27,56].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The levels of dopamine and adrenaline were unaffected in this study (but were elevated in plasma). There are also some studies with conflicting results published [8,19,27,56].…”
Section: Discussionmentioning
confidence: 99%
“…It should also be remembered that SCS is often effective in pain syndromes which are considered relatively in sensitive to opioids. Only in one study by Tonelli et al [19] were there some patients displaying a release of (5-Iipotropin and [3-endorphin in lumbar CSF following SCS. There are also several investigators who have been unable to find any increase in endogenous opioids in CSF after SCS [20].…”
Section: Introductionmentioning
confidence: 99%
“…Also, in 1988, Tonelli et al found low CSF-BE in patients scheduled for Spinal Cord Stimulation (SCS), compared to historic controls [238]. As a contrast, in 1988, Vaeroy et al found normal levels of CSF-BE in fibromyalgia syndrome patients [244].…”
Section: Neuropeptidesmentioning
confidence: 99%
“…Concerning CSF-BE, longitudinal studies before and after an invasive intervention have yielded inconclusive results, and/or results that are difficult to interpret due to the nature of the intervention [87,238]. In one of these studies [87], mean CSF-BE decreased by 56% in 9 patients 12-17 days after successful treatment with Dorsal Root Entry Zone Lesions.…”
Section: The Temporal Variation Of Csf-bementioning
confidence: 99%
See 1 more Smart Citation